EVALUATION OF ELECTRIC CONDUCTIVITY OF CARBON POWDER CARBURIZERS - Yury M. Dombrovskiy; Makar S. Stepanov; Galina I. Brover (Advanced Engineering Research, 2011)
The probability of metal ware carburizing in the carbon-wearing powdered media under passing current through the powdered environment and the workpiece is considered. The effect of the powered coke dispersibility on the electrical resistance of the powder saturating medium is shown.